2007
DOI: 10.1097/01.ncq.0000263105.08096.b1
|View full text |Cite
|
Sign up to set email alerts
|

Families Speak About Inpatient End-of-Life Care

Abstract: Death is an emotional event that leaves lasting memories for the bereaved. This article describes the qualitative analysis of a mailed family survey addressing experiences with community hospital inpatient end-of-life care. Family members identified and appreciated symptom management and caring behaviors such as compassion and communication; they also noted the absence of these caring behaviors. Effective application of these behaviors to the dying experience should improve family satisfaction with end-of-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The interaction between informal and professional care at the end of life is of crucial importance for family members (Andershed, 2006;Heyland et al, 2006;London & Lundstedt, 2007). In the encounter with professional care, family carers take with them their previous experiences of informal care, illness, and death and, in addition, their unique knowledge about the sick person.…”
mentioning
confidence: 99%
“…The interaction between informal and professional care at the end of life is of crucial importance for family members (Andershed, 2006;Heyland et al, 2006;London & Lundstedt, 2007). In the encounter with professional care, family carers take with them their previous experiences of informal care, illness, and death and, in addition, their unique knowledge about the sick person.…”
mentioning
confidence: 99%
“…The importance of giving attention to how we communicate with patients can also have a positive impact on perceptions by patients and families. Patients and families express a feeling of increased dignity when they recognize the impact the discussion has on the clinician (London & Lundstedt, 2007). Research findings suggest increased satisfaction with care when respect is demonstrated.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Research findings suggest increased satisfaction with care when respect is demonstrated. High marks for satisfaction with care have also been received regarding compassion when respect is shown by the team (London & Lundstedt, 2007;Murphy & Aquino-Russel, 2008). Some authors emphasize that when attention is not given to communicating in a way that facilitates the narrative content, one has the potential to increase the patient's suffering and inability to express the lived experience in a meaningful way (Ferrell & Coyle, 2008;Yang et al, 2010).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations